Advertisement Remove all ads

Solve the Following Equation: ("X" - 1)/("7x" - 14) = ("X" - 3)/("7x" - 26) - Mathematics

Sum

Solve the following equation:

`("x" - 1)/("7x" - 14) = ("x" - 3)/("7x" - 26)`

Advertisement Remove all ads

Solution

`("x" - 1)/("7x" - 14) = ("x" - 3)/("7x" - 26)`

⇒ (x - 1)(7x - 26) = (7x - 14)(x - 3)

⇒ 7x2 - 7x - 26x + 26 = 7x2 - 14x - 21x + 42

⇒ -33x + 26 = -35x + 42

⇒ 35x - 33x = 42 - 26

⇒ 2x = 16

⇒ x = 8

  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

Selina Concise Mathematics Class 8 ICSE
Chapter 14 Linear Equations in one Variable
Exercise 14 (A) | Q 22 | Page 166
Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×